Pengaruh Pengalaman Kerja, Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan Pada CV Aneka Berkah Ukur - Alif Dimas Ramdani; Ubaidillah Zuhdi; Nuzulul Fatimah; Dwi Novitasari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Companies are required to provide optimal service, so having quality employees is an important aspect in supporting the company's reputation and value in the eyes of the public. Quality employees will reflect a positive image of the company and contribute to the achievement of organizational goals. Therefore, factors such as work experience, compensation, and work motivation need to be considered so that employees are able to maintain and improve their performance. This shows that it is important for employees to pay attention to Work Experience, Compensation and Work Motivation so that employees can maintain their performance. This study aims to determine the effect of work experience, compensation and work motivation on employee performance at CV Aneka Berkah Ukur. This research method uses a quantitative method with an associative approach. The sample or respondents taken were 45 employee respondents. This study uses saturated sampling techniques. While the data analysis technique for this study is multiple linear regression with the help of SPSS software. The results of this study indicate that work experience, compensation, and work motivation simultaneously affect employee performance at CV Aneka Berkah Ukur. This study is also expected to contribute to improving employee performance at CV Aneka Berkah Ukur.